SOCIAL PRACTICE PERFORMED BY BALINESE SCULPTORS IN DISTRICTS OF UBUD AND SUKAWATI TO PRY INTO THE LAW OF PHORNOGRAPHY - Sudita, I Ketut (E-Journal of Cultural Studies; Volume 6, Number 1, May 2013)
Balinese sculptors in districts of Ubud and Sukawati, Gianyar, Bali pry into the Law of Pornography. Those who agree state that the law is needed to maintain the morality which has been getting worse, and those who disagree state that it may emasculate their freedom and creativities. This study gives answers to (1) what social practices were performed by the Balinese sculptors to pry into the Law of Pornography?, (2) why did they pry into the application of the law?, and (3) what was the meaning of their prying? Several relevant critical theories such as the theory of structuration, the theory of hegemony, and the theory of aesthetics were eclectically used in this study. The data needed were collected through observation, in-depth interview, documentation study, and library research. The result of the study showed that the Balinese sculptors showed their resistance to the application of the law by making adaptation, changing profession, and still producing pornographic works. The sanction which might be imposed upon them, the consumers of pornographic works decreased, and they were eliminated from exhibitions scared them when they pried into the law. What they did could not be separated from economic, political, ideological, moral, and ethic factors. The meaning of their prying was that it caused them to lose their idealism, their consumers went down, and the number of pornographic works dropped as well.
Keywords: social practices, Balinese sculptors, hegemony, the Law of Pornography.